El análisis de las historias de los hogares - Mei Ling Young (Estudios sobre las Culturas Contemporáneas)
A methodological and theorethical discussion about the significance of women in the Malaysian economy. Particularly focussed in the notable feature of Malaysian households under the pressure of urbanization and the family change in the modem world. Young considers the lives and family relationships of young, working Malaysian women in Malaysia, with their divided loyalties, yet continued sharing of earnings with families left in the villages.